Zakat in the View of Islamic Economics - Supriyadi, Supriyadi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This paper aims to describe zakat from an Islamic economic perspective using qualitative methods, through literature study. That zakat from an Islamic economic perspective has significant potential, so zakat needs to receive more attention from the government as is the urgency of zakat in the welfare of society. Finally, zakat can be an alternative solution for community welfare and a source of foreign exchange for the country. So zakat not only has religious value, but zakat also has significant economic value.